THE EFFORTS TO IMPROVE MATHEMATICAL LEARNING OUTCOMES WITH INQUIRY LEARNING STRATEGY IN PARTICIPANTS - Sri Mulyani Subekti; Anggit Prabowo (Universitas Ahmad Dahlan, 2019)
The limited role of students when learning mathematics results in students not being able to actualize the abilities that are in the students optimally. One of these abilities, namely the cognitive abilities of students. This study aims to improve mathematics learning outcomes with inquiry learning strategies in students of class VIII odd semester of SMP Muhammadiyah Sewon, Bantul District, 2018/2019 school year. This research is a Class Action Research (CAR). This study's subjects were class VIII-A students of Junior High School (SMP) Muhammadiyah Sewon, Bantul District, 2018/2019 school year. Simultaneously, the object in this study is the result of learning mathematics in class VIII-A students. Data is collected through observation, interviews, daily test tests, and also documentation. Data analysis used qualitative descriptive data analysis. The results of the study show that inquiry learning strategies can improve mathematics learning outcomes for students. From the results of observations that have been made during the study, there is an increase in mathematics learning outcomes for students in the learning process. In the first cycle, the average value of student learning outcomes is 67.97, and the percentage of classical learning completeness is 62.50%. There was an increase in the average value of student learning outcomes in the second cycle, 71.09, and the percentage of classical learning completeness became 71.88%. From the results of daily tests held at the end of each cycle, it can be concluded that there is an increase in student learning outcomes.